Nilai-Nilai Filosofis dalam Tradisi Rajaban di Kesultanan Kanoman Cirebon - Naila Farah (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
Cirebon is one of the centers of Islamic civilization in the past. This is at least evidenced by the founding of the Sultanate of Cirebon in the 15th century AD. The Sultanate of Cirebon plays a major role in spreading Islam in the western region of Java. Under the Sultanate of Cirebon Islamic traditions grow and flourish in society. Although the Sultanate of Cirebon split into two parts namely Kasepuhan Sultanate and Kanoman Sultanate, but the traditions are still preserved. Among these traditions is the tradition of Rajaban, a tradition that is held on 27 Rajab each year which aims to commemorate the events of Isra Mi’raj Prophet Muhammad SAW. Implementation of Islamic tradition in Cirebon is currently getting a pretty fierce challenge both from Islamic circles themselves, i.e. from the purification of Islam, as well as from the flow of globalization that tends to leave something that is considered ancient and traditional. This paper shows that the Rajaban tradition is still preserved by Kanoman Sultanate and Cirebon people. The procession of the Rajaban tradition itself is done with the core event of the reading of Isra Mi’raj chronicle, which is delivered in the old Cirebon language. The tradition of Rajaban can survive in the midst of various obstacles because it is still considered to have value by the community. The values include a pleasure value, vital value, spiritual value and value of holiness.